Héritages de Byzance en Europe du Sud-Est à l'époque moderne et contemporaine - Delouis, Olivier; Couderc, Anne; Guran, Petre (Mondes méditerranéens et balkaniques (MMB), 2013)
The Byzantine civilisation has left a lasting mark on individuals and societies of South-Eastern Europe. After the fall of Constantinople in 1453 it lost the frame, the Byzantine Empire, in which it had flourished for more than a millennium. Although restrained by a new power, the Ottoman Empire, Byzantine legacies never disappeared but survived in memories and traditions, in history and faith, in formal or informal institutions. And when peoples formerly included in the Byzantine Empire or subject to its influence established themselves as nations, when they started writing their past and considered what could be their European fate - from the Enlightenment, but especially in the 19th and 20th centuries - Byzantium was naturally reconsidered, reassessed, reinvented. The aim of this collective book is to study in a comparative manner, thanks to scholars of all countries, the history of the memory of Byzantium in South-Eastern Europe. A conclusion emerges: neither a nostalgia nor a curiosity, Byzantium appears as one of the foundations of modern Europe.